Determination of neurometabolism in patients with mild and moderate cognitive impairments - N. N. Mikheev; M. V. Zharikova; L. V. Eliseeva; Yu. V. Borisova (Вестник рентгенологии и радиологии)
Objective: to estimate the diagnostic value of neuropower mapping (NPM) and positron emission tomography (PET) and their relationships in the evaluation of neurometabolism in patients with predementia cognitive impairments.Material and methods. The investigation enrolled 125 patients with clinical signs of cognitive impairments. The patients were divided into 4 groups: 1) predementia cognitive impairments (PCI) in the presence of cerebrovascular disease (CVD); 2) PCI in the presence of  psychoautonomic syndrome (PAS); 3) PCI in the presence of sequels to acute cerebrovascular accident (SCVA); 4) PCI in the presence of toxic, dysmetabolic, hypoxic encephalopathies (TDHEP). All the patients underwent NPM and 55 patients had PET.Results and discussion. NPM and PET revealed neurometabolic disturbances in 100 and 46,3% of cases, respectively. The sensitivity of NPM was significantly higher than that of PET. The highest number of diffuse and diffuse-focal hypometabolism cases (n = 19 (63,3%)) were seen in the CVD and SCVA groups.Conclusion. 1. NPM and PET assess two aspects of brain  neurometabolism. 2. PET hypometabolism characterizes either structural organic abnormalities in the brain in the presence SCVA or initial manifestations of the neurodegenerative process. 3. NPM  readings characterize the activity, strength of metabolic responses, that is to say, cerebral reactivity. 4. PET readings are important in determining the prognosis of disease and NPM ones are essential in defining drug treatment policy.